FRI0257 Augmented Concentrations of Cx3cl1 Are Associated with Progressiv Interstitial Lung Disease in Systemic Sclerosis. (15th July 2016) - Hoffmann-Vold, A.-M.; Huynh, R.; Volkmann, E.; Palchevskiy, S.; Midtvedt, Ø.; Garen, T.; Der Hovanessian, A.; Weigt, S.; Fishbein, M.; Ardehali, A.; Ross, D.; Saggar, R.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a complex, immune-mediated disorder that carries high risk for progressive interstitial lung disease (ILD). CX3CL1 (Fractalkine) is expressed in lungs; and has the ability to act as an adhesion molecule as well as a potent chemoattractant of mononuclear cells via its interaction with CX3CR1. Here, we hypothesized that the CX3CL1/CX3CR1 axis could play an important role in the immune pathogenesis of SSc associated ILD. Objectives: (i) To explore CX3CL1 concentrations in lung homogenates from patients with SSc-ILD at the time of lung transplant (LT) compared to donor lung homogenates with no lung disease. (ii) To test whether CX3CL1 concentrations in serum differ between SSc patients and healthy controls. (iii) To assess associations between serum CX3CL1 and the development of SSc-ILD. Methods: Lung tissue was collected at LT from SSc (n=12) and donor lungs (n=12) at the UCLA. Concentrations of CX3CL1 in lung homogenates were determined by Luminex technology. Cellular sources of CX3CL1were assessed by immunohistochemistry (IHC). Sera from the prospective Oslo University Hospital SSc cohort (n=240) and healthy controls (n=100) were analysed for CX3CL1 concentration by ELISA. Paired pulmonary function tests (PFTs) and HRCT images were obtained at baseline and follow-up. Non-parametric statistical analysis was performed via Kruskal-Wallis testing. Categorical data were analyzed by Chi-squared testing. Predictive values were analyzed by multivariate linear regression and cox regression. Results: Concentrations of CX3CL1 in lung homogenates and serum were increased in SSc compared to healthy controls (Table 1 ). IHC demonstrated a CX3CL1 co-localization with reactive type II pneumocytes, airway epithelial cells, epithelial cells involved in bronchiolization, and infiltrating mononuclear cells. Serum CX3CL1 was significantly associated with anti-Topoisomerase I antibody and extensive ILD (Table 1 ). Linear regression analyses showed associations between CX3CL1 and extent of lung fibrosis at follow up (Regression coefficient (B): 0.86, SE 0.41, p=0.038) when adjusting for age and gender. Cox regression analysis showed predictive associations of CX3CL1 to extensive ILD (HR 1.43, 95% CI 1.02–1.26, p=0.017) and to ΔDLCO% decline >7.5% (HR 1.13, 95% CI 1.02–1.25, p=0.023). However, following further adjustment, including PFT parameters and autoantibodies, CX3CL1 was no longer significant. Conclusions: We have demonstrated an association between elevated protein levels of CX3CL1 in SSc-ILD and have shown that within the lungs, CX3CL1 are predominately co-localized with epithelia and infiltrating mononuclear cells. Augmented concentrations in the serum of SSc patients may be predictive of ILD. Disclosure of Interest: None declared